2019
DOI: 10.1186/s12935-019-0905-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circRNA–miRNA–mRNA regulatory network in gastric cancer by analysis of microarray data

Abstract: Background: Evidence is increasingly indicating that circular RNAs (circRNAs) are closely involved in tumorigenesis and cancer progression. However, the function of circRNAs in gastric cancer (GC) are still unknown. Here, we aimed to determine the regulatory mechanism of circRNAs in GC. Methods: Expression profiles of circRNAs were downloaded from four Gene Expression Omnibus (GEO) microarray datasets. Expression profiles of miRNAs and mRNAs were collected from The Cancer Genome Atlas (TCGA) database. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 34 publications
4
67
0
Order By: Relevance
“…Besides, Sun et al and Guan et al also performed bioinformatical analysis for circRNAs in hepatocellular carcinoma and gastric cancer, which used different methods and studied the ceRNA in different angles. 31,32 Thus, it would be reasonable to believe that bioinformatics provide guidance for our study. Certainly, further rigorous experiments are necessary to validate these findings.…”
Section: Dovepressmentioning
confidence: 99%
“…Besides, Sun et al and Guan et al also performed bioinformatical analysis for circRNAs in hepatocellular carcinoma and gastric cancer, which used different methods and studied the ceRNA in different angles. 31,32 Thus, it would be reasonable to believe that bioinformatics provide guidance for our study. Certainly, further rigorous experiments are necessary to validate these findings.…”
Section: Dovepressmentioning
confidence: 99%
“…The function of hsa_circ_0005699 in cancer was controversial. hsa_circ_0005699 was previously reported to downregulate MCM8 and NCAPD2 expression by acting as a sponge of hsa-miR-504, functioning as tumor suppressor in gastric cancer [29]. Our study suggested that hsa_circ_0005699 may promote PTC as a sponge of hsa-miR-139-3p and upregulate SPC24 and CDKN2A expression.…”
Section: Discussionmentioning
confidence: 50%
“…The DEGs from all gene microarray datasets and RNA-seq data were obtained using the RRA method. This method uses a probabilistic model for aggregation, which is resilient to noise, and can calculate the probability of signi cance of all elements and perform the nal ranking [33][34][35][36][37]. The cutoff P value for the RRA was set as 0.05.…”
Section: The Potential Mechanism Of Bsg Expression In Thyroid Cancer mentioning
confidence: 99%